Implementation of Transcendental-Based Juvenile Criminal Sanctions - Agatha Jumiati (Law Doctoral Program Universitas Muhammadiyah Surakarta, 2021)
The development of law in Indonesia is carried out based on the noble values contained in the precepts of Pancasila. These noble values are actually an inseparable part of transcendental values. Transcendental thought is an alternative to answer the failure of the positivistic view in solving legal problems in society. Regarding the implementation of juvenile criminal sanctions which commit criminal acts as regulated by Law number 11 of 2012 concerning the Juvenile Criminal Justice System, it turns out that in its regulation it has implemented transcendental values by placing child as noble creatures created by God who must always be guided and protected even though they have been or have committed a mistake or crime. Regulations on diversion, restorative justice, strengthening the role of the correctional center and the types of crimes that are humane are evidence that the implementation of juvenile criminal sanctions in Indonesia has contained transcendental values. Keywords: Implementation of Sanctions, Transcendental, Juvenile Crime